2019
DOI: 10.1101/813915
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Bayesian polyvertex score (PVS-B): a whole-brain phenotypic prediction framework for neuroimaging studies

Abstract: The traditional brain mapping approach has greatly advanced our understanding of the localized effect of the brain on behavior. However, the statistically significant brain regions identified by the standard mass univariate models only explain minimal variance in behavior despite increased sample sizes and statistical power, highlighting the nonsparseness of the explanatory signal in the brain. We introduced the Bayesian polyvertex score (PVS-B), a wholebrain prediction framework that aggregates the effect siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…Currently, brain-wide association studies are trapped in the initial discovery phase. Larger samples will inevitably allow multivariate models, both those currently in use and future improvements currently being developed [38][39][40][41] , to be employed by individual research groups. Smaller, investigator-initiated neuroimaging studies will continue to be just as important for human neuroscience as they were in the days when samples of N>10,000 for brainwidewide association studies (BWAS) were still an impossibility.…”
Section: Towards Reproducible Brain-wide Association Studies Through mentioning
confidence: 99%
“…Currently, brain-wide association studies are trapped in the initial discovery phase. Larger samples will inevitably allow multivariate models, both those currently in use and future improvements currently being developed [38][39][40][41] , to be employed by individual research groups. Smaller, investigator-initiated neuroimaging studies will continue to be just as important for human neuroscience as they were in the days when samples of N>10,000 for brainwidewide association studies (BWAS) were still an impossibility.…”
Section: Towards Reproducible Brain-wide Association Studies Through mentioning
confidence: 99%
“…We recently demonstrated that there were significant associations between the regionalisation of CSA and CTH (when controlling for global structural measures) and the fluid and crystallised composite scores from the NIH Toolbox within the ABCD baseline sample using the Multivariate Omnibus Statistical Test: the MOSTest 24 . This test aggregates vertex-wise associations across the cortex thereby improving our power for detecting widely distributed effects compared to the standard neuroimaging approach [24][25][26] . Given the graded nature of the biology underlying the patterning of the cortex this is a more appropriate statistical approach compared to standard neuroimaging methods.…”
Section: Distinct Associations Between Cortical Morphology and Differmentioning
confidence: 99%
“…This allowed us to determine the unique association between relative cortical morphology and cognition and compare this to the predictive power of brain structure without controlling for global measures. The method used here is outlined in detail by Zhao and colleagues 25 . The association between each imaging phenotype and each cognitive task was modelled using the mass univariate approach such that the behaviour of interest was predicted independently at each vertex using a general linear model (GLM).…”
Section: Comparison Across Associations Mapsmentioning
confidence: 99%
“…Having discovered genomic loci in training folds, we perform replication of these loci in the test sets. To perform replication for each SNP we calculate a PolyVertex Score (PVS) (similar to (6,7)), to project the test imaging phenotype data to a single scalar value for each individual using projection weights learned in the training data. This approach is similar to the widely used method of Polygenic Risk Scores (PRS) in genetics(8), where instead of predicting a phenotype we are predicting a single genomic variant and instead of using distributed effects across the genome as predictors we use the distributed effects across the cortex, estimated in the training set.…”
Section: Introductionmentioning
confidence: 99%
“…Having discovered genomic loci in training folds, we perform replication of these loci in the test sets. To perform replication for each SNP we calculate a PolyVertex Score (PVS) (similar to (6,7)) from imaging data in the test set for each MOSTest discovered locus. This PVS aggregates the distributed effects across the cortex by taking a weighted sum across all vertices using mass univariate z statistics as weights from the training set.…”
Section: Introductionmentioning
confidence: 99%